Penerapan Media Flash Card dalam Peningkatan Penguasaan Kosakata Bahasa Arab Peserta Didik di Rumah Belajar Madani Yakesma - Indah Doa Nita Nasution; Hasrian Rudi Setiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim to be achieved in this research is to improve students' ability to memorize Arabic vocabulary at the Yakesma civil learning home. Another aim of using Flash Card media is to make learning effective and very optimal between reaction and motivation, students are very active and enthusiastic in memorizing Arabic vocabulary. This research uses qualitative methods, this type of research is field research, to obtain field data several methods are used, namely, direct observation, interviews and documentation. This research was conducted on students with a total of 20 students. The results of this research show that learning using flash card media improves students' memorization abilities and increases their mastery of Arabic vocabulary. Students find it easier to understand vocabulary using flash card media because they can see directly the images on the flash card. With the Flash Card method, students get direct learning experience so that learning is more interesting and avoids student boredom and can improve student learning outcomes. From the data, it can be recommended to teachers to use the Flash Card method, especially in learning Arabic, to improve students' mastery of Arabic vocabulary.